A kind of anti-ultraviolet and anti-aging temperature control fabric

Through the load nanotoxic titanium dioxide on the aramid III and microporous polyester fibers, the problem of the aramid fiber is easy to aging under ultraviolet light, realizing the efficient anti -ultraviolet rays and anti -aging performance of the fabric, which enhances its coloring and durability sex.

CN116289175BActive Publication Date: 2025-01-28HEYE HEALTH TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310286326.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-23
Publication Date
2025-01-28
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

Aramid fibers are prone to photoaging and degradation under long-term exposure to oxygen and ultraviolet light, causing defects such as fibers to become brittle and discolored, and cracks on the surface, affecting the life and application of the fibers.

Method used

By preparing titanium dioxide and loaded on the aramid III and microporous polyester fibers to form a fabric of anti -ultraviolet and anti -aging. This process includes the preparation of nano -titanium dioxide, fiber pre -processing and loading nano -titanium dioxide.

Benefits of technology

Improve the resistance of the fabric's anti -ultraviolet rays and anti -aging performance, and enhance its friction, soap resistance, light resistance and heat -resistant pressure coloring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116289175B_ABST
    Figure CN116289175B_ABST
Patent Text Reader

Abstract

The present invention relates to an anti-ultraviolet and anti-aging temperature control fabric. Its preparation process includes: preparation of nano-TiO2: mixing anhydrous ethanol and deionized water to prepare a hydrolyzate, mixing anhydrous ethanol, tetra-n-butyl titanate and concentrated nitric acid evenly to obtain a precursor solution, mixing the hydrolyzate with the precursor solution; dispersing solid titanium dioxide powder in anhydrous ethanol, taking the supernatant for standby use; fiber pretreatment: weighing aramid III and microporous polyester fiber for pretreatment; the pretreatment process is: placing aramid III and microporous polyester fiber in sodium hydroxide solution and treating them for a period of time under certain temperature conditions; preparation of in-situ nano-titanium dioxide aramid III / microporous polyester fiber; blended fabric. The fabric of the present invention has good hygroscopicity, water absorption, air permeability, light weight and warmth retention, fluffy and soft.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fabric, in particular to an anti-ultraviolet and anti-aging temperature body-sensing control fabric. Background Art

[0002] Microporous polyester fiber is a new type of functional fiber. It uses a special production process to form a honeycomb microporous structure inside the fiber, and introduces sulfonic acid groups and polyethylene glycol flexible segments into the fiber molecular structure, which enhances the fiber's moisture absorption and perspiration function and improves its dyeing performance and feel. Because the surface and cross-section of the honeycomb modified polyester fiber have microporous structures, the moisture absorption, water absorption, air permeability, and wrinkle elasticity of the fabric are better than those of ordinary polyester fabrics. At the same time, due to the porous structure, it is light and warm, and the feel is fluffy and softer than ordinary polyester fabrics, which comprehensively improves the wearing performance.

[0003] Aramid fiber, carbon fiber and high-strength polyethylene fiber are the three most productive high-performance fibers. As important reinforcing materials, they are widely used in composite materials. Aramid fiber is a new type of synthetic fiber with high strength, high temperature resistance, acid and alkali resistance, high modulus, light weight, good aging resistance and insulation. It is widely used in automobiles, aerospace equipment, optical fibers, cables, etc. It is an important strategic material that is indispensable for national security, economic construction and scientific and technological progress.

[0004] Most studies have found that long-term exposure to oxygen and ultraviolet light will cause photoaging and degradation, causing the fiber to become brittle and discolored, and cracks to form on the surface, resulting in a gradual decline in the mechanical properties of aramid products, affecting the life of the fiber and restricting its application. Therefore, it is necessary to improve the ability of aramid fibers to resist photodegradation. Summary of the invention

[0005] The purpose of the present invention is to provide an anti-ultraviolet and anti-aging temperature control fabric to solve the problems of light aging degradation, surface cracks and other defects that affect the life of the fiber and restrict its application.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions:

[0007] An anti-ultraviolet and anti-aging temperature control fabric comprises the following preparation steps:

[0008] Step (1) Preparation of nano-titanium dioxide

[0009] Anhydrous ethanol and deionized water are measured and mixed to prepare a hydrolyzate; anhydrous ethanol, tetrabutyl titanate and concentrated nitric acid are measured and mixed evenly to form a precursor solution. The hydrolyzate is mixed with the precursor solution and the temperature is maintained. The mixture is stirred by a constant temperature magnetic stirrer until TiO2 appears. The mixture is dried in a constant temperature environment to obtain nano-TiO2 powder.

[0010] The solid titanium dioxide powder obtained by the reaction is dispersed in anhydrous ethanol, stirred evenly, and placed in a high-speed centrifuge to be subjected to centrifugal force, and the supernatant is taken for later use;

[0011] Step (2) Fiber pretreatment

[0012] Weigh aramid III and microporous polyester fibers and perform pretreatment. The pretreatment process is as follows: place the aramid III and microporous polyester fibers in a sodium hydroxide solution and treat them for a period of time under certain temperature conditions. After the pretreatment, wash them with deionized water and dry them at low temperature to obtain pretreated aramid III and microporous polyester fibers;

[0013] Step (3) Preparation of nano-titanium dioxide loaded aramid III / microporous polyester fiber:

[0014] A certain amount of aramid III and microporous polyester fiber are immersed in the prepared hydrolyzing agent, placed in the precursor solution, and allowed to stand at the same temperature, immersed and rolled twice, and then dried, washed with deionized water and dried at low temperature to obtain nano-titanium dioxide-loaded aramid III / microporous polyester fiber;

[0015] Step (4) Preparation of fabric blending.

[0016] When the nano titanium dioxide of the present invention is prepared, the repulsion between the particles of the sol increases, and the dispersibility of the sol is better. Therefore, as the amount of nitric acid added to the reaction system decreases, the particle size of the generated titanium dioxide increases, and the titanium dioxide agglomerates fall and precipitate during high-speed centrifugation. The titanium dioxide remaining in the supernatant exhibits better dispersibility. Since nitric acid is added as an inhibitor in the reaction system, the generated titanium dioxide carries hydrogen ions, and the proton concentration in the liquid phase is relatively high. Since the titanium dioxide surface has a certain number of hydroxyl groups, the surface hydroxyl groups are easy to obtain protons to form -TiOH 2+ And positively charged;

[0017] The titanium dioxide in-situ loaded fiber of the present invention is first immersed in a hydrolyzing agent during the treatment process, and the hydrolyzing agent is a mixed liquid composed of deionized water, anhydrous ethanol and nitric acid, and its molecular weight is small enough to enter the fiber cell wall; after being rolled by a small rolling mill, an appropriate amount of uniform hydrolyzing agent remains on the fiber surface, and when the fiber is immersed in a precursor solution, it reacts with tetra-n-butyl titanate in the solution to generate a uniform titanium dioxide film in situ and load it on the fiber surface;

[0018] The invention can finally obtain a light, warm, fluffy and soft fabric. According to the test, the fabric has good color fastness to friction, soap washing, light and hot pressing. The titanium dioxide loaded fiber fabric prepared by a specific process has good anti-ultraviolet and anti-aging properties.

[0019] Preferably, step (1) preparation of nano titanium dioxide:

[0020] Measure 20-30 ml of anhydrous ethanol and 40-50 ml of deionized water respectively and mix them to prepare a hydrolyzate; measure 20-30 ml of anhydrous ethanol, 15-25 ml of tetrabutyl titanate and 1-3 ml of concentrated nitric acid and mix them evenly to form a light yellow liquid, which is called a precursor solution. Mix the hydrolyzate with the precursor solution and keep the temperature at 50-60°C, stirring with a constant temperature magnetic stirrer until a sol (TiO2) with a blue transparent light appears.

[0021] Drying in a constant temperature environment of 100°C will give light yellow nano-TiO2 powder.

[0022] Preferably, step (2) fiber pretreatment

[0023] Weigh 5-10g of aramid III and microporous polyester fibers for pretreatment. The pretreatment process is as follows: place the aramid III and microporous polyester fibers in a sodium hydroxide solution with a concentration of 10g / L and treat them at a temperature of 75-85°C for 30 minutes. After pretreatment, wash with deionized water until the residual liquid after washing is neutral, and dry at 60°C to obtain pretreated aramid III and microporous polyester fibers.

[0024] Preferably, step (3) is the preparation of nano-titanium dioxide loaded aramid III / microporous polyester fiber:

[0025] With a bath ratio of 1:20-1:30 (fiber: solvent), take 5-10g of aramid III and microporous polyester fiber and immerse it in the prepared hydrolyzing agent, let it stand at a constant temperature of 50-60℃ for 20-30min, place it in the precursor solution, let it stand at the same temperature, immerse it once and roll it twice, the rolling rate is 90%, after drying at 60℃, wash away the nano titanium dioxide floating on the fiber surface with deionized water and dry it at low temperature.

[0026] Among them, tetrabutyl titanate is used as a precursor to undergo a hydrolysis condensation reaction with water under acidic conditions, and titanium dioxide is generated in situ on the fiber surface.

[0027] Preferably, the step (4) fabric blending preparation includes loaded nano titanium dioxide aramid III / microporous polyester fiber, wool fiber---pre-opening------packing---cleaning and rolling---combing---pre-mixing and drawing (1)---drawing (2)---drawing (3)---coarse yarn---spinning---winding---drawing---twisting---winding.

[0028] Preferably, in step (4), the fabric blending is prepared as follows:

[0029] 3 kinds of fiber blending ratio: 80~85% of nano-titanium dioxide-loaded aramid III / microporous polyester fiber, 15~20% of wool fiber, 5~10% of 2D*38mm polyester-based black conductive fiber. The microporous polyester and conductive fiber premixed package is packed in a 10% ratio and arranged in a "plum blossom pile" form to enhance the uniformity of the blended cotton;

[0030] Roving process: adopt the process principle of "light weight and low speed". Mixing--6 slivers are combined. To ensure that the colored yarn does not have color difference, the slivers fed into the mixing and combining are placed crosswise according to the sliver can numbers of the carding machine; Mixing 2 and Mixing 3 are both combined with 8 slivers, so that the fibers are fully straightened, paralleled and mixed after the drawing process, and the yarn has no color difference;

[0031] Spinning process: using Siro compact spinning process, feeding according to double roving; the process principle is "low speed, large back zone spacing, small back zone drafting multiple, small jaw spacing";

[0032] Winding process: Autoconer 238 automatic winder is used as the winding equipment for microporous polyester-wool blended yarn;

[0033] Aramid III / microporous polyester wool blended fabric.

[0034] Preferably, in the preparation of nano-titanium dioxide loaded aramid III / microporous polyester fiber in step (3), a microporous fiber modification device is used, including a microporous fiber modification impregnation box, a bracket, a constraint ring, a movable column, a shaking plate, a connecting plate, a rotating shaft, a constraint roller, a tightening screw ring, a tightening screw and a twisting plate. The left and right sides of the top of the microporous fiber modification impregnation box are respectively connected to the bottom end of the constraint ring through a group of brackets, the inner wall of the constraint ring is rotatably connected to the outer wall of the movable column, the outer sides of the two groups of movable columns are respectively connected to one side of the inner end of a group of shaking plates, the inner ends of the two groups of movable columns are respectively connected to one side of the outer end of a group of connecting plates, the other sides of the inner ends of the two groups of connecting plates are respectively rotatably connected to the left and right ends of the rotating shaft, the outer wall of the rotating shaft is connected to the inner wall of the constraint roller, the top ends of the two groups of constraint rings are respectively connected to the bottom ends of a group of tightening screw rings, the inner wall of the tightening screw ring is screwed to the outer wall of the tightening screw, and the top of the tightening screw is connected to the middle of the bottom end of the twisting plate.

[0035] The microporous fiber modification device of the present invention also includes baffles, and the left and right sides of the restraining roller are respectively connected to the middle parts of the inner ends of a group of baffles.

[0036] The microporous fiber modification device of the present invention also includes a connecting rod, a connecting frame and a counterweight block. The upper sides of the inner ends of the two groups of connecting pieces are respectively connected to the left and right ends of the connecting rod, and the top end of the connecting rod is connected to the counterweight block via the connecting frame.

[0037] The microporous fiber modification device of the present invention also includes a handlebar and a turning handle. The top side of the outer end of the counterweight block is connected to the inner end of the handlebar, and the outer end of the handlebar is rotatably connected to the inner end of the turning handle.

[0038] The microporous fiber modification device of the present invention also includes a scale bar, and the scale bar is connected to the left front side of the microporous fiber modification impregnation box.

[0039] The microporous fiber modification device of the present invention also includes an information board, and the front side of the left end of the microporous fiber modification impregnation box is connected to the inner end of the information board.

[0040] The microporous fiber modification device of the present invention also includes an on-off valve and a drain pipe. The right rear side of the left end of the microporous fiber modification impregnation box is connected to the inner end of the on-off valve, and the outer end of the on-off valve is connected to the drain pipe.

[0041] The microporous fiber modification device of the present invention also includes a fixing plate. The lower ends of the left and right sides of the microporous fiber modification impregnation box are respectively connected to the inner ends of a group of fixing plates.

[0042] Compared with the prior art, the present invention has the following beneficial effects: simple operation and improved practicality.

[0043] In summary, the beneficial effects of the present invention are:

[0044] The fabric of the present invention has good color fastness to rubbing, color fastness to soaping, color fastness to light and color fastness to hot pressing.

[0045] In the preparation of nano-titanium dioxide loaded aramid III / microporous polyester fiber, a microporous fiber modification device is used. When in use, first shake the shaking plate to rotate the movable column in the constraint ring, so that the connecting plate is turned over, and then the bottom side of the shaking plate drives the rotating shaft and the constraint roller to turn upward, and the twisting plate is turned to rotate the top screw. The top screw is screwed with the top screw ring to tighten and fix the movable column inward, so that the position of the constraint roller is fixed, and the aramid III and microporous polyester fiber can be passed from the bottom side of the constraint roller. Then, the twisting plate is reversed to rotate the top screw. The top screw is screwed with the top screw ring and moves outward to loosen the movable column. The connecting plate can be turned over to drive the rotating shaft and the constraint roller to drive the material at the corresponding position downward to immerse in the hydrolyzing agent in the microporous fiber modification impregnation box. After that, the moving impregnation can be carried out under the rotation constraint of the rotating shaft and the constraint roller. The flipping and moving of the mechanism facilitates the preparation of the microporous fiber material, which is beneficial to improving the anti-ultraviolet and anti-aging properties of the fiber, thereby improving the corresponding properties of the fabric;

[0046] The titanium dioxide loaded fiber fabric prepared by a specific process has good anti-ultraviolet and anti-aging properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic axial view of the structure of a modification device for microporous fibers used in the preparation of the anti-ultraviolet and anti-aging temperature-sensing control fabric of the present invention;

[0048] Figure 2 The present invention Figure 1 The top view of

[0049] Figure 3 The present invention Figure 1 Front view of

[0050] Figure 4 This is a preparation process of an anti-ultraviolet and anti-aging temperature control fabric of the present invention;

[0051] Markings in the attached drawings: 1. microporous fiber modified impregnation box; 2. bracket; 3. constraint ring; 4. movable column; 5. rocker; 6. connecting plate; 7. rotating shaft; 8. constraint roller; 9. tightening screw ring; 10. tightening screw; 11. screw plate; 12. baffle; 13. connecting rod; 14. connecting frame; 15. counterweight; 16. handle; 17. turning handle; 18. scale bar; 19. information plate; 20. opening and closing valve; 21. drainage pipe; 22. fixing plate. Implementation

[0052] Example

[0053] Step (1) Preparation of nano titanium dioxide:

[0054] Measure 20ml of anhydrous ethanol and 40ml of deionized water respectively and mix them to prepare the hydrolyzate; measure 20ml of anhydrous ethanol, 15ml of tetrabutyl titanate and 1ml of concentrated nitric acid and mix them evenly, which is called the precursor solution. Mix the hydrolyzate with the precursor solution and keep the temperature at 50℃, stirring until a sol (TiO2) with a blue transparent light appears.

[0055] Drying in a constant temperature environment of 100°C will give light yellow nano-TiO2 powder.

[0056] Step (2) Fiber pretreatment

[0057] Weigh 5g of aramid III and microporous polyester fibers for pretreatment. The pretreatment process is as follows: place the aramid III and microporous polyester fibers in a sodium hydroxide solution with a concentration of 10g / L and treat them at a temperature of 75°C for 30min. After pretreatment, wash with deionized water until the residual liquid after washing is neutral, and dry at a low temperature of 60°C to obtain pretreated aramid III and microporous polyester fibers.

[0058] Step (3) Preparation of nano-titanium dioxide loaded aramid III / microporous polyester fiber:

[0059] With a bath ratio of 1:20 (fiber: solvent), 5g of aramid III and microporous polyester fiber were immersed in the prepared hydrolyzing agent, and allowed to stand at a constant temperature of 50°C for 20min. Then, the fiber was placed in the precursor solution and allowed to stand at the same temperature. The fiber was dipped once and rolled twice, and the rolling rate was 90%. After drying at 60°C, the nano-titanium dioxide floating on the fiber surface was washed off with deionized water and dried at low temperature.

[0060] Step (4) Fabric blending preparation:

[0061] According to the loading ratio of nano-titanium dioxide aramid III / microporous polyester fiber 80%, wool fiber 10%, 2D*38mm polyester-based black conductive fiber 5%. "Microporous polyester and conductive fiber premixed package" 10% is arranged in the form of "plum blossom piles". After the drawing process, roving process, spinning process, and winding process, the aramid III / microporous polyester and wool blended fabric is obtained.

[0062] Example 2

[0063] Step (1) Preparation of nano titanium dioxide:

[0064] Measure 23 ml of anhydrous ethanol and 43 ml of deionized water respectively and mix them to prepare a hydrolyzate; measure 23 ml of anhydrous ethanol, 16 ml of tetrabutyl titanate and 1.5 ml of concentrated nitric acid and mix them evenly, which is called a precursor solution. Mix the hydrolyzate with the precursor solution and keep the temperature at 53°C, stirring until a sol (TiO2) with a blue transparent light appears.

[0065] Drying in a constant temperature environment of 100°C will give light yellow nano-TiO2 powder.

[0066] Step (2) Fiber pretreatment

[0067] Weigh 6g of aramid III and microporous polyester fibers for pretreatment. The pretreatment process is as follows: place the aramid III and microporous polyester fibers in a sodium hydroxide solution with a concentration of 10g / L and treat them at a temperature of 78°C for 30min. After pretreatment, wash with deionized water until the residual liquid after washing is neutral, and dry at a low temperature of 60°C to obtain pretreated aramid III and microporous polyester fibers.

[0068] Step (3) Preparation of nano-titanium dioxide loaded aramid III / microporous polyester fiber:

[0069] With a bath ratio of 1:24 (fiber: solvent), 6g of aramid III and microporous polyester fiber were immersed in the prepared hydrolyzing agent, and allowed to stand at a constant temperature of 53°C for 23min. Then, they were placed in the precursor solution and allowed to stand at the same temperature. After one immersion and two rollings, the rolling rate was 90%. After drying at 60°C, the nano-titanium dioxide floating on the fiber surface was washed off with deionized water and dried at low temperature.

[0070] Step (4) Fabric blending preparation:

[0071] According to the loading ratio of nano-titanium dioxide aramid III / microporous polyester fiber 82%, wool fiber 12%, 2D*38mm polyester-based black conductive fiber 8%, and 10% of the "microporous polyester and conductive fiber premixed package", it is arranged in the form of "plum blossom piles". After the drawing process, roving process, spinning process, and winding process, the aramid III / microporous polyester and wool blended fabric is obtained.

[0072] Example 3

[0073] Step (1) Preparation of nano titanium dioxide:

[0074] Measure 25 ml of anhydrous ethanol and 45 ml of deionized water respectively and mix them to prepare a hydrolyzate; measure 25 ml of anhydrous ethanol, 20 ml of tetrabutyl titanate and 2 ml of concentrated nitric acid and mix them evenly, which is called a precursor solution. Mix the hydrolyzate with the precursor solution and keep the temperature at 55°C, stirring until a sol (TiO2) with a blue transparent light appears.

[0075] Drying in a constant temperature environment of 100°C will give light yellow nano-TiO2 powder.

[0076] Step (2) Fiber pretreatment

[0077] Weigh 8g of aramid III and microporous polyester fibers for pretreatment. The pretreatment process is as follows: place the aramid III and microporous polyester fibers in a sodium hydroxide solution with a concentration of 10g / L and treat them at a temperature of 80°C for 30min. After pretreatment, wash with deionized water until the residual liquid after washing is neutral, and dry at a low temperature of 60°C to obtain pretreated aramid III and microporous polyester fibers.

[0078] Step (3) Preparation of nano-titanium dioxide loaded aramid III / microporous polyester fiber:

[0079] 8 g of aramid III and microporous polyester fibers were immersed in the prepared hydrolyzing agent at a bath ratio of 1:25 (fiber: solvent), and allowed to stand at a constant temperature of 55°C for 25 min. They were then placed in the precursor solution and allowed to stand at the same temperature. The fibers were dipped once and rolled twice, with a rolling rate of 90%. After drying at 60°C, the nano-titanium dioxide floating on the fiber surface was washed off with deionized water and dried at low temperature.

[0080] Step (4) Fabric blending preparation:

[0081] According to the loading ratio of nano-titanium dioxide aramid III / microporous polyester fiber 83%, wool fiber 13%, 2D*38mm polyester-based black conductive fiber 8%, and 10% of the "microporous polyester and conductive fiber premixed package", it is arranged in the form of "plum blossom piles". After the drawing process, roving process, spinning process, and winding process, the aramid III / microporous polyester and wool blended fabric is obtained.

[0082] Example 4

[0083] Step (1) Preparation of nano titanium dioxide:

[0084] Measure 30ml of anhydrous ethanol and 50ml of deionized water respectively and mix them to prepare the hydrolyzate; measure 30ml of anhydrous ethanol, 25ml of tetrabutyl titanate and 3ml of concentrated nitric acid and mix them evenly, which is called the precursor solution. Mix the hydrolyzate with the precursor solution and keep the temperature at 60℃, stirring until a sol (TiO2) with a blue transparent light appears.

[0085] Drying in a constant temperature environment of 100°C will give light yellow nano-TiO2 powder.

[0086] Step (2) Fiber pretreatment

[0087] Weigh 10g of aramid III and microporous polyester fibers for pretreatment. The pretreatment process is as follows: place the aramid III and microporous polyester fibers in a sodium hydroxide solution with a concentration of 10g / L and treat them at a temperature of 85°C for 30min. After pretreatment, wash with deionized water until the residual liquid after washing is neutral, and dry at a low temperature of 60°C to obtain pretreated aramid III and microporous polyester fibers.

[0088] Step (3) Preparation of nano-titanium dioxide loaded aramid III / microporous polyester fiber:

[0089] With a bath ratio of 1:30 (fiber: solvent), 10g of aramid III and microporous polyester fiber were immersed in the prepared hydrolyzing agent, and allowed to stand at a constant temperature of 60°C for 30min. Then, the fiber was placed in the precursor solution and allowed to stand at the same temperature. The fiber was dipped and rolled twice, and the rolling rate was 90%. After drying at 60°C, the nano-titanium dioxide floating on the fiber surface was washed off with deionized water and dried at low temperature.

[0090] In the preparation of nano-titanium dioxide loaded aramid III / microporous polyester fiber in step (3), a microporous fiber modification device is used, such as Figures 1 to 3As shown, it includes a microporous fiber modified impregnation box 1, a bracket 2, a constraint ring 3, a movable column 4, a shaking piece 5, a connecting piece 6, a rotating shaft 7, a constraint roller 8, a tightening screw ring 9, a tightening screw 10 and a twisting piece 11. The left and right sides of the top of the microporous fiber modified impregnation box 1 are respectively connected to the bottom end of the constraint ring 3 through a group of brackets 2, the inner wall of the constraint ring 3 is rotatably connected to the outer wall of the movable column 4, the outer sides of the two groups of movable columns 4 are respectively connected to one side of the inner end of a group of shaking pieces 5, the inner ends of the two groups of movable columns 4 are respectively connected to one side of the outer end of a group of connecting pieces 6, the other sides of the inner ends of the two groups of connecting pieces 6 are respectively rotatably connected to the left and right ends of the rotating shaft 7, the outer wall of the rotating shaft 7 is connected to the inner wall of the constraint roller 8, the top ends of the two groups of constraint rings 3 are respectively connected to the bottom ends of a group of tightening screw rings 9, the inner wall of the tightening screw ring 9 is screwed to the outer wall of the tightening screw 10, and the top of the tightening screw 10 is connected to the middle part of the bottom end of the twisting piece 11; first shake the shaking piece 5, the movable column 4 is rotated in the constraint ring 3, the connecting piece 6 is turned over, and then the bottom side thereof drives the rotating shaft 7 and the constraint roller 8 to turn upward, the twisting piece 11 is twisted to rotate the tightening screw 10, and the tightening screw 10 is screwed with the tightening screw ring 9 to tighten and fix the movable column 4 inward, so that the position of the constraint roller 8 is fixed, and the aramid III and microporous polyester fibers can be passed through the bottom side of the constraint roller 8, and then the twisting piece 11 is reversed to rotate the tightening screw 10, and the tightening screw 10 is screwed with the tightening screw ring 9 to move outward to loosen the movable column 4, and the connecting piece 6 can be turned over to make the rotating shaft 7 and the constraint roller 8 drive the materials at the corresponding positions to be immersed downward into the hydrolyzing agent in the microporous fiber modified impregnation box 1, and then the movable column 4 can be moved and impregnated under the rotation constraint of the rotating shaft 7 and the constraint roller 8. The preparation of the microporous fiber material is convenient through the flipping and moving of the mechanism, the operation is simple, and the practicality is improved.

[0091] The microporous fiber modification device of the present invention also includes a baffle 12. The left and right sides of the constraint roller 8 are respectively connected to the middle of the inner end of a group of baffles 12; the baffles 12 can block the left and right sides of the constraint roller 8 to prevent the material from sliding outward, thereby improving reliability.

[0092] A microporous fiber modification device of the present invention also includes a connecting rod 13, a connecting frame 14 and a counterweight 15. The upper sides of the inner ends of the two groups of connecting plates 6 are respectively connected to the left and right ends of the connecting rod 13, and the top of the connecting rod 13 is connected to the counterweight 15 via the connecting frame 14. When the connecting rod 13 and the connecting frame 14 are connected, the connecting plate 6, the rotating shaft 7 and the restraining roller 8 can be balanced through the counterweight 15, which makes flipping more labor-saving and improves convenience.

[0093] A microporous fiber modification device of the present invention also includes a handle 16 and a turning handle 17. The top side of the outer end of the counterweight block 15 is connected to the inner end of the handle 16, and the outer end of the handle 16 is rotatably connected to the inner end of the turning handle 17. Holding the turning handle 17 and rotating it with the handle 16 can drive the shaking plate 5 to shake, thereby improving convenience.

[0094] The microporous fiber modification device of the present invention further includes a scale bar 18, and the scale bar 18 is connected to the left front side of the microporous fiber modification impregnation box 1; the scale bar 18 can indicate the liquid level, which is convenient for judging the corresponding reagent amount and improving convenience.

[0095] The microporous fiber modification device of the present invention also includes an information board 19. The front side of the left end of the microporous fiber modification impregnation box 1 is connected to the inner end of the information board 19. The information board 19 can display equipment information, which is convenient for reading and auxiliary use, thereby improving convenience.

[0096] A microporous fiber modification device of the present invention also includes an on-off valve 20 and a drain pipe 21. The right rear side of the left end of the microporous fiber modification impregnation box 1 is connected to the inner end of the on-off valve 20, and the outer end of the on-off valve 20 is connected to the drain pipe 21; opening the on-off valve 20 facilitates the discharge of the reagent in the microporous fiber modification impregnation box 1 through the drain pipe 21, thereby improving convenience.

[0097] The microporous fiber modification device of the present invention also includes a fixing plate 22. The lower ends of the left and right sides of the microporous fiber modification impregnation box 1 are respectively connected to the inner ends of a group of fixing plates 22; the device can be connected and fixed to the ground through the fixing plates 22 to improve stability.

[0098] The present invention discloses a device for modifying microporous fibers. When the device is in operation, the shaking blade 5 is first shaken to rotate the movable column 4 in the constraint ring 3, so that the connecting piece 6 is turned over, and then the bottom side of the shaking blade 11 is driven by the rotating shaft 7 and the constraint roller 8 to turn upward, and the tightening blade 11 is twisted to rotate the tightening screw 10. The tightening screw 10 is screwed together with the tightening screw ring 9 to tighten and fix the movable column 4 inward, so that the position of the constraint roller 8 is fixed, and the aramid III and microporous polyester fibers can be passed through the bottom side of the constraint roller 8, and then the tightening blade 11 is reversed to rotate the tightening screw 10. The tightening screw 10 is screwed together with the tightening screw ring 9 to move outward to loosen the movable column 4, and the connecting piece 6 can be turned over to make the rotating shaft 7 and the constraint roller 8 drive the materials at the corresponding positions to be immersed downward into the hydrolyzing agent in the microporous fiber modification impregnation box 1, and then the movable impregnation can be carried out under the rotation constraint of the rotating shaft 7 and the constraint roller 8.

[0099] Step (4) Fabric blending preparation:

[0100] According to the packing ratio of 85% of nano-titanium dioxide aramid III / microporous polyester fiber, 15% of wool fiber, and 10% of 2D*38mm polyester-based black conductive fiber, the "microporous polyester and conductive fiber premixed package" is arranged in the form of "plum blossom piles". After the drawing process, roving process, spinning process, and winding process, the aramid III / microporous polyester-wool blended fabric is obtained.

[0101] Comparative Example 1

[0102] Step (1) Preparation of nano titanium dioxide:

[0103] Measure 20ml of anhydrous ethanol and 40ml of deionized water respectively and mix them to prepare the hydrolyzate; measure 20ml of anhydrous ethanol, 15ml of tetrabutyl titanate and 1ml of concentrated nitric acid and mix them evenly, which is called the precursor solution. Mix the hydrolyzate with the precursor solution and keep the temperature at 50℃, stirring until a sol (TiO2) with a blue transparent light appears.

[0104] Drying in a constant temperature environment of 100°C will give light yellow nano-TiO2 powder.

[0105] Step (2) Fiber pretreatment

[0106] Weigh 5g of microporous polyester fiber and perform pretreatment. The pretreatment process is as follows: place aramid III and microporous polyester fiber in a sodium hydroxide solution with a concentration of 10g / L and treat at a temperature of 75°C for 30min. After pretreatment, wash with deionized water until the residual liquid after washing is neutral, and dry at a low temperature of 60°C to obtain pretreated microporous polyester fiber.

[0107] Step (3) Preparation of nano-titanium dioxide loaded microporous polyester fibers:

[0108] 5 g of microporous polyester fiber was immersed in the prepared hydrolyzing agent at a bath ratio of 1:20 (fiber: solvent), and allowed to stand at a constant temperature of 50°C for 20 min. It was then placed in the precursor solution and allowed to stand at the same temperature. The fiber was immersed and rolled twice, and the rolling rate was 90%. After drying at 60°C, the nano-titanium dioxide floating on the fiber surface was washed off with deionized water and dried at low temperature.

[0109] Step (4) Fabric blending preparation:

[0110] According to the packing ratio of 80% of nano-titanium dioxide microporous polyester fiber, 10% of wool fiber, and 5% of 2D*38mm polyester-based black conductive fiber, the "microporous polyester and conductive fiber premixed package" is arranged in the form of "plum blossom piles". After the drawing process, roving process, spinning process, and winding process, the aramid III / microporous polyester and wool blended fabric is obtained.

[0111] Comparative Example 2

[0112] Step (1) Preparation of nano titanium dioxide:

[0113] Measure 20ml of anhydrous ethanol and 40ml of deionized water respectively and mix them to prepare the hydrolyzate; measure 20ml of anhydrous ethanol, 15ml of tetrabutyl titanate and 1ml of concentrated nitric acid and mix them evenly, which is called the precursor solution. Mix the hydrolyzate with the precursor solution and keep the temperature at 50℃, stirring until a sol (TiO2) with a blue transparent light appears.

[0114] Drying in a constant temperature environment of 100°C will give light yellow nano-TiO2 powder.

[0115] Step (2) Fiber pretreatment

[0116] Weigh 5g of aramid III and perform pretreatment. The pretreatment process is as follows: place the aramid III in a sodium hydroxide solution with a concentration of 10g / L and treat it at a temperature of 75°C for 30min. After the pretreatment, wash it with deionized water until the residual liquid after washing is neutral, and dry it at a low temperature of 60°C to obtain the pretreated aramid III.

[0117] Step (3) Preparation of nano-titanium dioxide loaded aramid fiber III:

[0118] With a bath ratio of 1:20-1:30 (fiber: solvent), take 5-10g of aramid III and immerse it in the prepared hydrolyzing agent, let it stand at a constant temperature of 50-60℃ for 20-30min, place it in the precursor solution, let it stand at the same temperature, immerse it once and roll it twice, the rolling rate is 90%, after drying at 60℃, wash away the nano titanium dioxide floating on the fiber surface with deionized water and dry it at low temperature.

[0119] Step (4) Fabric blending preparation:

[0120] According to the loading ratio of nano titanium dioxide aramid III 80-85%, wool fiber 10-15%, 2D*38mm polyester-based black conductive fiber 5-10%, "microporous polyester and conductive fiber premixed package" 10% is arranged in the form of "plum blossom piles". After the drawing process, roving process, spinning process, and winding process, aramid III / microporous polyester wool blended fabric is obtained.

[0121] Performance test of the products of the embodiments and comparative examples:

[0122] UV protection

[0123] This project is tested in accordance with GB / T 18830-2009 Evaluation of UV Protection of Textiles to determine the UVA, UVB and UPF values ​​of fabrics.

[0124] Color fastness to heat pressing

[0125] This project is tested in accordance with GB / T 6152-1997 Textiles - Tests for colour fastness - Colour fastness to hot pressing.

[0126] Moisture wicking and quick drying performance

[0127] This project was tested in accordance with GB / T 21655.1-2008 Evaluation of moisture absorption and quick-drying properties of textiles Part 1: Single combination test method. The experiment used Zhejiang Fangyuan Instrument Co., Ltd.'s FFZ191-Ⅱ moisture evaporation rate meter, YG871-ⅡA capillary effect tester and YG501D-Ⅱ moisture permeability tester.

[0128] Color fastness to rubbing

[0129] This project was tested in accordance with GB / T 3920-2008 Textiles - Tests for colour fastness - Colour fastness to rubbing, and the experiment used the Y571F rubbing colour fastness tester produced by Zhejiang Fangyuan Instrument Co., Ltd.

[0130] Color fastness to soap washing

[0131] This project was tested in accordance with method A (1) of GB / T 3921-2008 Textiles - Tests for colour fastness - Colour fastness to washing with soap and soap. The experiment used the SW-24A colour fastness to washing tester produced by Zhejiang Fangyuan Instrument Co., Ltd.

[0132] Color fastness to light

[0133] This project was tested in accordance with Method 3 of GB / T 8427-2008 Textiles - Tests for colour fastness - Colour fastness to artificial light: Xenon arc fading lamp. The experiment used the Q-sun Xe-2-H sunlight and weathering colour fastness tester from Luozhong Technology (Shanghai) Co., Ltd.

[0134]

[0135]

[0136]

[0137]

[0138] As shown in Tables 1 to 4, Example 4 has the best effect, with color fastness to rubbing 4.2, color fastness to soaping 4.4, color fastness to light 4.8, and color fastness to hot pressing 3.8, while those of Comparative Example 2 are 3.0, 3.0, 3.3, and 3.0, respectively. The fabric has the characteristics of "cotton": soft, delicate, skin-friendly, and soft luster; the characteristics of "wool": crisp, full, resilient, and diffuse luster; the characteristics of "numbing and refreshing": moisture absorption and perspiration, quick drying, cool, and not close to the body.

[0139]

[0140] As can be seen from Table 5, Example 4 has the best effect, with UPF, UVA, and UVB of 85, 1.8, and 0.3 respectively, while Comparative Example 2 has the worst results, with UPF, UVA, and UVB of 52, 5.2, and 1.5 respectively. This ultraviolet absorption performance of titanium dioxide-loaded fibers proves from the side that it has anti-ultraviolet performance. This is because the reaction system synthesizes titanium dioxide at room temperature, and the titanium dioxide formed is composed of crystalline and non-crystalline titanium dioxide. High temperature is conducive to increasing the random motion between the reactant molecules, thereby increasing the molecular kinetic energy, and is conducive to increasing the proportion of crystalline titanium dioxide, thereby improving the anti-ultraviolet performance of cotton fabrics. Since anhydrous ethanol is used as a solvent for the precursor solution, its boiling point is 78.4°C. When the reaction temperature increases, the ethanol in the reaction system partially evaporates. As the treatment time increases, the crystalline titanium dioxide gradually grows complete, thereby improving the anti-ultraviolet performance of the fabric. As the reaction time is further extended, the thickness of the titanium dioxide film generated on the fiber surface will also increase excessively, and the bonding strength between the fiber and the titanium dioxide film will decrease. When the fiber is subsequently washed and strongly combed during the spinning process, the titanium dioxide loaded on the fiber surface will fall off, which is manifested as a decrease in the UPF value of the fabric.

[0141]

[0142] As shown in Table 6, these results can be attributed to the photostabilization effect of nano-TiO2 particles on the surface, which prevents ultraviolet light from degrading CN organic bonds. The volume of nano-TiO2 decreases with the continuous absorption of ultraviolet light, until the ultraviolet light disappears and continues to destroy the amide bonds of the fiber, resulting in a decrease in the mechanical properties of the fiber. The above results show that the in-situ preparation of TiO2 on the surface and the fiber / microfiber interface alleviates the speed of aramid light aging. At the same time, the more TiO2 content on the fiber surface and the smaller the size, the better the anti-light aging effect on the fiber. This means that the prepared TiO2 has fewer defects, confirming the protective effect of nano-TiO2. The nano-TiO2 particles formed on the fiber surface can absorb and shield a large amount of ultraviolet light, thereby better preventing ultraviolet light from damaging the fiber. TiO2 can provide the best anti-light aging protection for fabrics.

[0143] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. An anti-ultraviolet and anti-aging temperature control fabric, characterized in that The preparation process includes: Step (1) Preparation of nano-titanium dioxide Measure 20-30 ml of anhydrous ethanol and 40-50 ml of deionized water respectively and mix them to prepare a hydrolyzate; measure 20-30 ml of anhydrous ethanol, 15-25 ml of tetra-n-butyl titanate and 1-3 ml of concentrated nitric acid, mix them evenly to form a light yellow liquid, which is called a precursor solution; Step (2) Fiber pretreatment Weigh 5-10g of aramid III and microporous polyester fibers for pretreatment; the pretreatment process is as follows: place the aramid III and microporous polyester fibers in a sodium hydroxide solution with a concentration of 10g / L, and treat them at a temperature of 75-85°C for 30min; after the pretreatment, wash them with deionized water until the residual liquid after washing is neutral, and dry them at a low temperature of 60°C to obtain the pretreated aramid III and microporous polyester fibers; Step (3) Preparation of nano-titanium dioxide loaded aramid III / microporous polyester fiber: 5-10 g of aramid III and microporous polyester fiber are immersed in the prepared hydrolyzing agent at a bath ratio of 1:20-1:30, and allowed to stand at a constant temperature of 50-60°C for 20-30 min. The fiber is then placed in a precursor solution and allowed to stand at the same temperature. The fiber is then immersed and rolled twice, and the rolling rate is 90%. After drying at 60°C, the nano-titanium dioxide floating on the fiber surface is washed off with deionized water and dried at low temperature to obtain nano-titanium dioxide-loaded aramid III / microporous polyester fiber. Step (4) Fabric blending preparation includes Loaded with nano titanium dioxide aramid III / microporous polyester fiber, wool fiber---pre-opening---packing---blowing and rolling---carding---pre-mixing and drawing (1)---drawing (2)---drawing (3)---roving---spinning---winding---doubling---twisting---winding; Among them, the blending ratio of three kinds of fibers: 80~85% of nano-titanium dioxide-loaded aramid III / microporous polyester fiber, 15~20% of wool fiber, 5~10% of 2D*38mm polyester-based black conductive fiber; the packing ratio of "microporous polyester and conductive fiber premixed package" is 10%, arranged in the form of "plum blossom piles" to enhance the uniformity of cotton blending; Among them, the sum of the proportions of nano-titanium dioxide aramid III / microporous polyester fiber, wool fiber, and polyester-based black conductive fiber is less than 100%; Roving process: adopt the process principle of "light weight and low speed"; Blending---adopt 6-strip merging. To ensure that the colored yarn does not have color difference, the slivers fed into the blending machine are placed crosswise according to the sliver can number of the carding machine; Blending 2 and Blending 3 both adopt 8-strip merging, so that the fibers are fully straightened, paralleled and mixed after the drawing process, and the yarn has no color difference; Spinning process: using Siro compact spinning process, feeding according to double roving; the process principle of "low speed, large back zone spacing, small back zone drafting multiple, small jaw spacing"; Winding process: Autoconer 238 automatic winder is used as the winding equipment for microporous polyester-wool blended yarn; Aramid III / microporous polyester wool blended fabric.

2. The method for producing anti-ultraviolet and anti-aging temperature-sensing control fabrics according to claim 1, characterized in that: Step (1) Preparation of nano titanium dioxide: The hydrolyzate was mixed with the precursor solution and stirred by a constant temperature magnetic stirrer while maintaining the temperature at 50-60°C until a sol TiO2 with a blue transparent light appeared; Drying in a constant temperature environment of 100°C will yield light yellow nano-TiO2 powder; The solid titanium dioxide powder obtained by the reaction is dispersed in anhydrous ethanol, stirred evenly, and placed in a high-speed centrifuge. After being subjected to the centrifugal force, the supernatant is taken out for later use.

3. The method for producing anti-ultraviolet and anti-aging temperature-sensing control fabrics according to claim 2, characterized in that: In the preparation of nano-titanium dioxide-loaded aramid III / microporous polyester fiber in step (3), a microporous fiber modification device is used, including a microporous fiber modification impregnation box (1), a bracket (2), a constraint ring (3), a movable column (4), a shaking plate (5), a connecting plate (6), a rotating shaft (7), a constraint roller (8), a tightening screw ring (9), a tightening screw rod (10) and a twisting plate (11). The left and right sides of the top of the microporous fiber modification impregnation box (1) are respectively connected to the bottom of the constraint ring (3) through a group of brackets (2), and the inner wall of the constraint ring (3) and the outer wall of the movable column (4) are rotated. The outer sides of the two groups of movable columns (4) are respectively connected to one side of the inner end of a group of rocking pieces (5), the inner ends of the two groups of movable columns (4) are respectively connected to one side of the outer end of a group of connecting pieces (6), the other sides of the inner ends of the two groups of connecting pieces (6) are respectively rotatably connected to the left and right ends of the rotating shaft (7), the outer wall of the rotating shaft (7) is connected to the inner wall of the constraint roller (8), the top ends of the two groups of constraint rings (3) are respectively connected to the bottom ends of a group of tightening screw rings (9), the inner wall of the tightening screw ring (9) is screwedly connected to the outer wall of the tightening screw rod (10), and the top end of the tightening screw rod (10) is connected to the middle part of the bottom end of the screw piece (11).

4. The method for producing anti-ultraviolet and anti-aging temperature-sensing control fabrics according to claim 3, characterized in that: The microporous fiber modification device also includes baffles (12), and the left and right sides of the restraining roller (8) are respectively connected to the middle parts of the inner ends of a group of baffles (12).

5. The method for producing anti-ultraviolet and anti-aging temperature-sensing control fabrics according to claim 4, characterized in that: The microporous fiber modification device also includes a connecting rod (13), a connecting frame (14) and a counterweight (15), wherein the upper inner ends of the two groups of connecting plates (6) are respectively connected to the left and right ends of the connecting rod (13), and the top end of the connecting rod (13) is connected to the counterweight (15) via the connecting frame (14).

6. The method for producing anti-ultraviolet and anti-aging temperature control fabrics according to claim 5, characterized in that: The microporous fiber modification device also includes a handlebar (16) and a turning handle (17), wherein the top side of the outer end of the counterweight (15) is connected to the inner end of the handlebar (16), and the outer end of the handlebar (16) is rotatably connected to the inner end of the turning handle (17).

Citation Information

Patent Citations

  • Multi-functional training clothes fabric for special police

    CN101302677A

  • Super-strong twisted double-strand yarn spinning process

    CN111877015A